Hip disorders in cerebral palsy patients: diagnostic and therapeutic approaches - Karslıoğlu, Bülent; Tekin, Ali Çagrı; Taşatan, Ersin; Erkin, Fatih Mehmet (The European Research Journal, 2018)
Cerebral palsy (CP) is a neurological disorder of central nervous system that can result with devastating outcomes. Besides all other clinical findings, hip disorders also are common in children with CP. Clinical hip manifestations include wide spectrum from hip subluxation or dislocation to dislocation with painful degeneration. If untreated they may progress to more serious level like painful hip, severe hip contractures or windswept deformity and cause hygiene problems. We aimed to present current and widely accepted information about diagnostic and therapeutic approaches of hip disordes in the patients with CP.